Implementasi Google Data Studio Pada Visualisasi Data Bola Bass Ball dalam Bentuk Dashboard - Suparmadi; Manurung, Nuriadi (Fakultas Ilmu Komputer, Universitas Pasir Pengaraian, 2024)
In the field of sports, the use of information technology is used to support performance in a sport. Data visualization is the answer to simplifying complex data into a graphical format so that it's easier to understand the data. Data management for one sport is an important process that must be carried out by sports. With good data management, the company gets more value. This added value is like decision support information, in order to be able to increase operational efficiency and effectiveness. This research uses data from one of the sports branches, Bass ball, items obtained from the internet, namely 2426 data. The research was conducted with the help of Google Data Studio tools for making dashboards. The results obtained are that there are several elements that help in making it easier to read information, namely scorecard elements, Pie Chart elements, bar chart elements, geographic chart elements, and table elements. The Record count element displays the total number of records, the average number of players, On the Pie Chart displays product insights in percent, the average attendance is obtained. The bar chart element displays the total player attendance each month, the player with the highest attendance being in May